2007
DOI: 10.1038/sj.npp.1301644
|View full text |Cite
|
Sign up to set email alerts
|

The Promnesic Effect of G-protein-Coupled 5-HT4 Receptors Activation Is Mediated by a Potentiation of Learning-Induced Spine Growth in the Mouse Hippocampus

Abstract: Pharmacological modulation of synaptic efficacy is a prominent target in the identification of promnesic compounds. Here, we report that pretraining administration of the serotonin 5-HT 4 receptors (5-HT 4 Rs) partial agonist SL65.0155 enhances simultaneous olfactory discrimination performance and potentiates learning-induced dendritic spine growth in the mouse hippocampus. SL65.0155 does not affect spine density in the pseudo-trained mice and, by itself, does not promote spine growth. Injecting the 5-HT 4 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 35 publications
2
28
1
Order By: Relevance
“…As demonstrated before (Roman et al, ; Jourquin et al, ; Chaillan et al, ; Restivo et al, ,b; ; Nivet et al, ), the OTM is a very useful apparatus that allows to efficiently assess hippocampus‐dependent task. Indeed, inversely to most of the olfactory discrimination tasks where the involvement of the hippocampal system is not requested, the integrity of the mouse hippocampi is needed to be successful in the OTM.…”
Section: Discussionmentioning
confidence: 78%
“…As demonstrated before (Roman et al, ; Jourquin et al, ; Chaillan et al, ; Restivo et al, ,b; ; Nivet et al, ), the OTM is a very useful apparatus that allows to efficiently assess hippocampus‐dependent task. Indeed, inversely to most of the olfactory discrimination tasks where the involvement of the hippocampal system is not requested, the integrity of the mouse hippocampi is needed to be successful in the OTM.…”
Section: Discussionmentioning
confidence: 78%
“…There is some evidence demonstrating spine morphological plasticity with learning [20][21][22][23][24][25], as well as evidence that the converse hypothesis may be true; that is, failure of spine formation and morphological plasticity may contribute to impairments in cognition [26]. Additional support for the latter hypothesis comes from studies that report alterations of spine numbers and morphology in animal models of aging [27][28][29][30][31][32] or neurodegenerative disease [33][34][35][36][37][38][39], both of which are characterized by compromised cognitive function.…”
mentioning
confidence: 73%
“…2). Pretraining stimulation of 5-HT 4 Rs has been reported to improve memory (Restivo et al, 2008) also in Flinders sensitive line rats when applied pretraining (Eriksson et al, 2012) and 5-HT 4 R antagonists have been reported to impair PA in mice when applied post-training (Galeotti et al, 1998). Hence, it is likely that 5-HT 1A R blockade results in a b Fig.…”
Section: Discussionmentioning
confidence: 94%